Absence of clinical benefit of FDG PET-CT in staging T1 part-solid lung adenocarcinoma. Issue 3 (March 2022) - Pencharz, D.; Modi, S.; Bandyopadhyay, S.; Alhun, U.; Marchbank, N.; Patel, A.; Wagner, T.
Abstract : AIM: To assess the rates of nodal and metastatic disease and change in management when staging part-solid T1 lung adenocarcinomas using integrated 2-[ 18 F]-fluoro-2-deoxy-d- glucose (FDG) positron-emission tomography (PET)–computed tomography (CT) in a UK population. MATERIALS AND METHODS: This was a retrospective review of PET-CT examinations performed to stage radiologically suspected T1 part-solid lung adenocarcinoma ( n= 58) from two different centres. Rates of detection of nodal and metastatic disease, change in management, and final patient outcome were recorded. RESULTS: PET-CT changed the stage in one patient from N0 to N1. It did not change final management in any patient. CONCLUSIONS: In this UK population, PET-CT had minimal additional diagnostic benefit in staging patients with T1 part-solid lung adenocarcinoma. Especially given its cost, the inclusion of PET-CT for this indication in guidelines should be reviewed. Highlights: FDG PET-CT has very low clinical benefit in staging T1 subsolid lung adenocarcinoma. FDG PET-CT likely has very poor cost effectiveness in staging T1 subsolid NSCLC. Guidelines advising FDG PET-CT for staging all curable NSCLC should be reviewed.